2015
DOI: 10.3345/kjp.2015.58.12.505
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar rhabdomyosarcoma with massive disseminated intravascular coagulopathy treated with systemic chemotherapy

Abstract: It is uncommon for pediatric patients with rhabdomyosarcoma to present with clinical and/or laboratory features of disseminated intravascular coagulation (DIC). We report a case of metastatic alveolar rhabdomyosarcoma with severe bleeding because of DIC in a 13-year-old boy. He experienced persistent oozing at the site of a previous operation, gross hematuria, and massive epistaxis. Two weeks after initiating combination chemotherapy consisting of vincristine, doxorubicin, and cyclophosphamide, the patients' l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The current case presented with persistent oozing at the site of puncture after BM biopsy. Aida et al and Yoon et al reported that DIC rapidly worsened after surgery or biopsy in patients with ARMS metastatic to BM. Therefore, invasive procedures and surgery require caution in these patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current case presented with persistent oozing at the site of puncture after BM biopsy. Aida et al and Yoon et al reported that DIC rapidly worsened after surgery or biopsy in patients with ARMS metastatic to BM. Therefore, invasive procedures and surgery require caution in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Severe DIC can occur in ARMS with BM metastasis and may be triggered by biopsy or invasive surgery . Exposure of the subendothelial tissue factor after trauma to the tumor blood vessels causes the release of cytokines with procoagulant activity.…”
Section: Discussionmentioning
confidence: 99%